2008
DOI: 10.3382/ps.2008-00122
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Hypoxia on Hatching Performance in Chickens with Different Genetic Adaptation to High Altitude

Abstract: The experiments were conducted to assess how hatching performance is affected by chicken breeds and environment of high altitude and to analyze the vital factor of the low hatchability at a 2,900-m altitude. Eggs of Tibetan and Dwarf chickens were incubated at conditions of normobaric normoxia, normobaric hypoxia, hypobaric hypoxia, and supplemental O2 at high altitude (hypobaric normoxia) during the whole incubation or at 0 to 7, 8 to 14, and 15 to 22 d of incubation, respectively. The results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
2
21
0
1
Order By: Relevance
“…The highest embryo mortality was recorded in the first seven days of incubation and on hatching, according to the results reported in Cobb breeders (Pedroso et al, 2005) and Tibetan and Dwarf breeds (Zhang et al, 2008). Our data confirm that the first 6-7 days of incubation and the hatching period are the most critical periods for the survival of chicken embryos.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The highest embryo mortality was recorded in the first seven days of incubation and on hatching, according to the results reported in Cobb breeders (Pedroso et al, 2005) and Tibetan and Dwarf breeds (Zhang et al, 2008). Our data confirm that the first 6-7 days of incubation and the hatching period are the most critical periods for the survival of chicken embryos.…”
Section: Discussionsupporting
confidence: 77%
“…Similar fertility data were recorded in poultry strains and other breeds; for instance, 77.5%-97.4% in the Cobb strain (Pedroso et al, 2005) and 89.9%-93.5% and 91.6%-95.4% in the Tibetan and Dwarf bantam breeds, respectively (Zhang et al, 2008). The best fertility values were recorded in March and this could be the month with the major reproductive efficiency of this breed.…”
Section: Discussionsupporting
confidence: 61%
“…More recent studies also showed high hypoxic sensitivity of embryonic metabolism and growth during early development in hypoxia. Collectively, these data suggest that there is a discrete threshold of O 2 availability that is required to both initiate and sustain early embryo development (Altimiras and Phu, 2000;Sharma et al, 2006), and that O 2 available during early incubation is important for hatch-ability (Zhang et al, 2008). However, some studies reported that chronic hypoxia (14% O 2 ) during the first 10 d of incubation had no effect on the weight of the embryo and its organs at the time of hatching (Miller et al, 2002), that the middle third of embryogenesis was critical for the effect of long-term hypoxia on metabolism (Dzialowski et al, 2002) or that the last week of incubation was sensitive for ventilatory response to hypoxia (Ferner and Mortola, 2009).…”
Section: Hypoxic Levels and Durationsmentioning
confidence: 96%
“…Due to adaptability to hypoxia, supplemental O 2 is a good way to improve hatchability and chick quality. Zhang et al (2008) indicated that breeding chickens adapted to HA (a 2900 m altitude) had a lower egg water loss and greater hatchability when they were incubated in hypoxic conditions. The findings of this study indicated that O 2 supplementation to the incubator after middle to last stages of embryogenesis could increase hatchability and decrease embryonic mortality because of the lowest egg water loss.…”
Section: Discussionmentioning
confidence: 99%